A computational study on H2S release and amide formation from thionoesters and cysteine. Issue 23 (28th May 2019) - Jiang, Yuan-Ye; Zhu, Ling; Fan, Xia; Zhang, Qi; Fu, Ya-Jie; Li, He; Hu, Bing; Bi, Siwei
Abstract : A computational study clarified the detailed mechanisms of H2 S release and amide bond formation from thionoesters and cysteine. Abstract : The recognition of the biological activity of H2 S has drawn much attention to the development of biocompatible H2 S release reactions. Thiol-, particularly cysteine-triggered systems which mimic the enzymatic conversion of cysteine or homocysteine to H2 S have been intensively reported recently. Herein, a density functional theory (DFT) study was performed to address the reaction mechanism of H2 S release and potential amide bond formation from thionoesters and cysteine to gain deeper mechanistic insights. Three possible mechanisms were considered and we found that the one starting from the nucleophilic addition of the ionized mercapto of cysteine on thionoester to generate a dithioester intermediate (Path A) is kinetically favored over the others starting from the nucleophilic addition of the amine of cysteine to generate thionoamide intermediates (Paths B and C). Dithioester then undergoes intramolecular nucleophilic addition of an amine group and the rate-limiting water-assisted proton transfer to generate a cyclic thiol intermediate, and finally affords H2 S and dihydrothiazole via water-assisted elimination. The hydrolysis of thionoamide or dihydrothiazole to produce amide is highly difficult under neutral conditions but is operative under strong basic conditions, which explains the experimental observation that dihydrothiazole rather than amide is the major product. Meanwhile, the ring opening reaction of the cyclic thiol intermediate to form the more stable thionoamide is detrimental to H2 S release and becomes competitive under basic conditions.